Współpraca na pograniczu polsko-niemieckim w latach 1989-1993 - polskie dyskusje i koncepcje = Cooperation in the Polish-German borderland in the years 1989-1993 - Polish discussions and concepts - Glinka, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The perspectives of development of co-operation on the Polish-German borderland in the first years of the Third Republic of Poland (1989-1993) became, as it was in case of Germany, the subject of interest of domestic policy-makers and researchers. Thus, on the one hand it is justified to present the shape and character of political discussions about this topic which were held among political environments. On the other hand, it is well-founded to show the ideas of development of contacts in the area of the borderland which were formulated by scientists.
Keywords: stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia; po 1944 r.